MARKETING AND ADVERTISING STRATEGY IN ACHIEVING THE TOP OF MIND (SAMSUNG BRAND CASE STUDY) - Andhita Vidya Putri; Eriyanto . (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Technological progress and competition between companies in the globalization era is increasing. New media plays an increasingly important role in advertising and marketing. In addition, the companies’ survival depends on the presence of audiences/consumers. Therefore, determining how to utilize this new media/technology and determining how effective and efficient digital advertising and marketing strategies so that advertising has an appeal to the audience and the products offered are acceptable to the audience and right on target, and in accordance with the specified target is important and interesting to study. To obtain a framework of important concepts and the best strategy of effective marketing and advertising, the author utilizes the literature review method with qualitative approach. In doing advertising and marketing, it is important to pay attention to the objectives, audience, and distribution / media of advertising and marketing. The use of various media such as social media, online advertising, digital signage, and also endorsers are also important factors in advertising and marketing success. Advertising and marketing strategies help to better understand consumers and see how best to engage and empower the audience / consumers to get what they want. Here technology has created a new environment, where power has shifted from advertisers to consumers. This research produced a variety of important strategies and the best media which can succeed advertising and marketing, attract audiences, obtain the AIDA (Attention Interest Desire Action) effect of the audience and finally reach the Top of Mind.